Private life and privacy in Nazi Germany - Harvey, Elizabeth; Hürter, Johannes; Umbach, Maiken; Wirsching, Andreas (2019)
Introduction: Reconsidering private life under the Nazi dictatorship / Elizabeth Harvey, Johannes Hurter, Maiken Umbach and Andreas Wirsching – A particular kind of privacy : accessing 'the private' in national socialism / Janosch Steuwer – Private lives, public faces : on the social self in Nazi Germany / Mary Fulbrook – Private and public moral sentiments in Nazi Germany / Nicholas Stargardt – (Re-)inventing the private under national socialism / Maiken Umbach – Private life in the people's economy : spending and saving in Nazi Germany / Pamela E. Swett – 'Hoist the flag!' : flags as a sign of political consensus and distance in the Nazi period / Karl Christian Fuhrer – The vulnerable dwelling : local privacy before the courts / Annemone Christians – Walther Von Hollander as an advice columnist on marriage and the family in the Third Reich / Lu Seegers – Personal relationships between harmony and alienation : aspects of home leave during the Second World War / Christian Packheiser – Working on the relationship : exchanging letters, goods, and photographs in wartime / Andrew Stuart Bergerson, Laura Fahnenbruck and Christine Hartig – Love letters from front and home : a private space for intimacy in the Second World War? / Cornelie Usborne – 'A birth is nothing out of the ordinary here ... ' : mothers, midwives and the private sphere in the 'Reichsgau Wartheland' 1939-1945 / Wiebke Lisner – Transformations of the 'private' : proximity and distance in the spatial confinement of the Ghettos in occupied Poland 1939-1942 / Carlos A. Haas